What Does the Future Hold for Maine’s Lobster Industry? - Acheson, James; Acheson, Ann (Maine Policy Review, 2020)
The Maine lobster industry is one of the most successfully managed fisheries in the world. Catches have been at record high levels since the 1990s due to favorable environmental factors, regulations enacted over a period of years, and the conservation ethic of fishermen. The industry faces problems that threaten its future: shell disease, climate change, increased regulations to protect right whales, and economic uncertainty. Several approaches could help protect the lobster industry, including enacting lower trap limits, expanding markets for live and processed lobster, and increasing in-state processing capacity. The latter two are already underway, but prospects for lower trap limits are uncertain.